Pengaruh Citra Merek dan Influencer Marketing Terhadap Keputusan Pembelian Pada Produk Glad2glow di Tiktok - Fatimah, Apsari Indriani; Nurlenawati, Netti; Triadinda, Dexi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
The industry, especially in the field of care and beauty, has begun to grow rapidly in Indonesia, due to the innovation of new products so that various types of promotion methods are needed, one of which is promotion through social media, especially on TikTok. TikTok was chosen because it has the largest number of users compared to other platforms, and has a large influence of influencer content on products. So that it can allow companies to compete in an increasingly tight market and provide good sales until a good perception of the brand is formed. The purpose of this study is to analyze the influence and importance of these two variables on what customers buy, and to provide information to brands to help them create more successful social media marketing campaigns. Researchers used a quantitative approach with 100 respondents as TikTok users and at least once saw the Glad2Glow promotion. This study used a questionnaire distributed online on Google Form. All data analyzed using SPSS 25 tools and multiple linear regression. The study findings show that influencer marketing and brand image significantly and positively influence consumer decisions to buy. Influencer marketing has a greater influence than brand image, especially when using famous influencers. Therefore, the product must have a strong brand image and the right influencer marketing, so that it can increase product sales.